Android-Based Digital Teaching Materials on the Topic of Changes in the Shape of Elementary School Class V Objects - Ni Kadek Juniari; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2022)
The teaching materials available in schools are not for the needs of students. The teaching materials used in schools are only copies of student books so that in the learning process, students do not get additional information. The purpose of this development research is to develop android-based digital teaching materials on changing the shape of objects in grade V elementary school. This type of research is the development of the ADDIE research model. The research subjects were 2 learning media experts, 2 learning content experts, and 2 teachers. The test subjects were 10 students. The data collection method used is a questionnaire. The instrument used in collecting data is a questionnaire. The data analysis technique is descriptive qualitative and quantitative analysis. The results of the research are media validity is very good, material validity is very good, the practicality of practitioners/teachers is very good, and student practicality is very good. The results showed that android-based digital teaching materials on the topic of changing the shape of objects in class V elementary schools were categorized as suitable for use in the learning process on changing objects in class V elementary schools.